Some solutions to complete mixed promotion policy for GEM-TVT products of Thai Van Tuong electromechanical construction joint stock company = Một số giải pháp nhằm hoàn thiện chính sách xúc tiến hỗn hợp cho sản phẩm Gem-TVT của công ty cổ phần chế tạo xây - Lê, Duy Tuấn, 1994- (2020)
Research the theory of marketing concept, mixed promotion strategy and how to formulate a marketing strategy for a product. Learn about grounding products in general and chemicals to reduce soil resistance in particular, the market of reducing electricity resistance in Vietnam. Analysis of the status and assessment of Marketing strategy of GEM-TVT products in Thai Van Tuong Electromechanical Construction Joint Stock Company. Proposing measures to improve Marketing strategy for GEM-TVT products of Thai Van Tuong Electromechanical Construction Joint Stock Company.